2021
DOI: 10.1093/neuonc/noab300
|View full text |Cite
|
Sign up to set email alerts
|

Dual IGF1R/IR inhibitors in combination with GD2-CAR T-cells display a potent anti-tumor activity in diffuse midline glioma H3K27M-mutant

Abstract: Background Diffuse midline gliomas (DMG) H3K27M-mutant, including diffuse intrinsic pontine glioma (DIPG), are pediatric brain tumors associated with grim prognosis. Although GD2-CAR T-cells demonstrated significant anti-tumor activity against DMG H3K27M-mutant in vivo, a multimodal approach may be needed to more effectively treat patients. We investigated GD2 expression in DMG/DIPG and other pediatric high-grade gliomas (pHGG) and sought to identify chemical compounds that would enhance GD2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 40 publications
0
32
0
Order By: Relevance
“…To verify that these immunocompetent DMG mouse models can be employed for the development of immunotherapies, we analyzed the expression of the disialoganglioside GD2 and Interleukin-13 receptor subunit alpha-2 (IL13Rα2), two antigens highly expressed in DMG tissues and identified as promising targets for immunotherapy in DMG. 28 , 31–34 For Il13rα2, we could confirm expression in both histone 3 wildtype and K27M-mutant DMG tissues, although a slightly lower and more heterogenous expression was observed for histone 3 wildtype tumors ( Supplementary Figure 9A ). For GD2, flow cytometry analysis indicated that this antigen is also expressed in our murine DMG cells, irrespective of their histone mutational status ( Supplementary Figure 9B ).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…To verify that these immunocompetent DMG mouse models can be employed for the development of immunotherapies, we analyzed the expression of the disialoganglioside GD2 and Interleukin-13 receptor subunit alpha-2 (IL13Rα2), two antigens highly expressed in DMG tissues and identified as promising targets for immunotherapy in DMG. 28 , 31–34 For Il13rα2, we could confirm expression in both histone 3 wildtype and K27M-mutant DMG tissues, although a slightly lower and more heterogenous expression was observed for histone 3 wildtype tumors ( Supplementary Figure 9A ). For GD2, flow cytometry analysis indicated that this antigen is also expressed in our murine DMG cells, irrespective of their histone mutational status ( Supplementary Figure 9B ).…”
Section: Resultsmentioning
confidence: 79%
“…GD2 immunophenotyping was performed by incubating cells for 30 min at 4°C with PE-conjugated anti-GD2 antibody (clone 14.G2a) (1:100; #562100, BD Biosciences) in staining buffer (0.2% BSA in PBS) in the dark, as described previously. 28 Flow cytometric analysis was performed on a CytoFLEX S Flow Cytometer (Beckman Coulter).…”
Section: Methodsmentioning
confidence: 99%
“…de Billy et al. combined IGF1R/IR inhibitors with GD2-CAR-T cells and saw increased antitumor activity from the combination in DMG cell lines ( 126 ). Exploring the combination of RTK therapy with MDSC inhibition, immune checkpoint inhibition, or CAR-T cell therapy could effectively increase the activation of CD8+ T-cells and change the TME to favor anti-tumor responses.…”
Section: Discussionmentioning
confidence: 99%
“…PROM2 is sensitive to insulin-like growth factor I receptor inhibitor linsitinib ( Fernando et al, 2021 ), insulin-like growth factor 1 inhibitor GSK1904529A ( Zeng et al, 2021 ), the estrogen receptors alpha antagonist AZD9496 ( Cani et al, 2021 ), and the dual-acting estrogen action inhibitor SR16157 ( Rausch et al, 2011 ). Among them, linsitinib has been reported to have potent antitumor activity in diffuse midline glioma when combined with modified chimeric antigen receptor T-cells ( de Billy et al, 2021 ); GSK1904529A has also been found to inhibit glioma tumor growth, induce apoptosis, and inhibit migration ( Zhou et al, 2015 ), and AZD9496; and SR16157 are potential drugs for treating breast cancer that are present in the early stages of clinical research ( Zhang et al, 2021 ) ( Rausch et al, 2011 ). GCH1 is sensitive to ribavirin, a synthetic nucleoside analogue with broad antiviral activity ( Jurković et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%